Association between Anthropometric Index and serum level of Vitamin D, Calcium, Mg, Alp and PTH in Women at Reproductive Age - Hamideh Mohaddesi; Shahsanam Gheibi; Marzieh Saei Ghare naz; Maryam Najarzadeh; Hamid Reza Khalkhali; Mitra Yeganehpoor (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2018)
Introduction: Today, modern lifestyle exposes women to a variety of vitamin deficiencies, and enzymes and hormones disorders, and then, obesity and overweight concerns. This study was performed with aim to determine the relationship between anthropometric index and serum level of vitamin D, calcium, magnesium, alkaline phosphatase, and parathyroid hormone. Methods: This correlational study was performed on 100 healthy women at reproductive age from Nov 2016 to Dec 2017 in Urmia. After obtaining the written consent and completing the questionnaire containing demographic information from the subjects, 10 ml of venous blood was taken after 12 hours of fasting. The levels of calcium, magnesium, vitamin D, parathyroid hormone and alkaline phosphatase and anthropometrics were measured. Data was analyzed using SPSS software (version 22) and correlation test and variance analysis. P< 0.05 was considered statistically significant. Results: In this study, vitamin D had a negative correlation with all anthropometric indices, but this correlation was not statistically significant (P>0.05). Calcium and magnesium had no significant correlation with anthropometric indices. Alkaline phosphatase had a positive but insignificant correlation with all anthropometric indices (p>0.05). In this study, PTH value had a significant positive correlation with BMI (r = 0.21, p<0.05). Conclusion: Among the measured indices, parathyroid hormone had a significant correlation with body mass index, and although the serum level of magnesium and calcium had a desirable level in most cases, but unfortunately, more than half of the samples suffered from vitamin D deficiency. Therefore, it is recommended that interventional program be performed for women of reproductive age to improve their vitamin D status.42w